Percutaneous snare-retrieval of intracardiac thrombus under fluoroscopic and transesophageal echocardiography guidance: case report and systematic review - Zhou, Huaji; Wang, Bing; Pan, Jun; Qiu, Chenyang; Yu, Xinyu; He, Yangyan; Zhu, Qianqian; Yu, Lei; Wu, Ziheng; Li, Donglin; Zhang, Hongkun (Frontiers in Cardiovascular Medicine, 2023)
Intracardiac foreign bodies (IFB) are rare clinical conditions. There are now several reports on the percutaneous retrieval of IFB under fluoroscopy. However, some IFB are not radiopaque, and retrieval requires combined fluoroscopic and ultrasound guidance. We report the case of a bedridden 23-year-old male patient with T-lymphoblastic lymphoma treated with long-term chemotherapy. Ultrasound examination diagnosed a huge thrombus in the right atrium near the opening of the inferior vena cava which affected the patency of his PICC line. Ten days of anticoagulant therapy did not modify the thrombus size. Open heart surgery was not feasible because of the patient clinical condition. Snare-capture of the non-opaque thrombus was done from the femoral vein under fluoroscopic and ultrasound guidance with excellent outcomes. We also present a systematic review of IFB. We found out that percutaneous removal of IFBs is a safe and effective procedure. The youngest patient who received percutaneous IFB retrieval was 10 days old and weighed only 800g, while the oldest patient was 70 years old. Port catheters (43.5%) and PICC lines (42.3%) were the most commonly found IFBs. Snare catheters and forceps were the most commonly used instruments.